2001
DOI: 10.1021/tx010067f
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Pattern Recognition Studies on the Time-Related Metabolic Effects of α-Naphthylisothiocyanate on Liver, Urine, and Plasma in the Rat:  An Integrative Metabonomic Approach

Abstract: We present here a novel integrative metabonomic approach to probe toxic effects of drugs in experimental animals using alpha-naphthylisothiocyanate (ANIT) as a model hepatotoxicant. Male Han-Wistar rats were dosed with ANIT (150 mg/kg, n = 25), and plasma and liver samples were collected for NMR and magic-angle spinning (MAS) NMR spectroscopy at 3, 7, 24, 31, and 168 h postdosing. Urine was collected continuously for 3 days prior to dosing and up to 168 h postdose. Histopathology and plasma clinical chemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
166
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(177 citation statements)
references
References 33 publications
11
166
0
Order By: Relevance
“…The results suggested that the induction of lipid degradation removed excessive lipids. Similar decreases in lipids that were accompanied by increases in lipid catabolism products were also observed in the livers of rats treated with alpha-naphthylisothiocyanate and high doses of triadimefon (Waters et al, 2001;Ekman et al, 2006).…”
Section: Effects Of Me Treatment Alone and Me Plus Vit E Cotreatment supporting
confidence: 68%
“…The results suggested that the induction of lipid degradation removed excessive lipids. Similar decreases in lipids that were accompanied by increases in lipid catabolism products were also observed in the livers of rats treated with alpha-naphthylisothiocyanate and high doses of triadimefon (Waters et al, 2001;Ekman et al, 2006).…”
Section: Effects Of Me Treatment Alone and Me Plus Vit E Cotreatment supporting
confidence: 68%
“…Other recent studies in rats have demonstrated that NMR-based metabonomic techniques can permit visualization of key time periods in the development of toxic injury enabling the identification of lesionspecific, matrix-specific biomarkers of cholestasis and hepatotoxicity. 74 Further work, especially studies using NMR spectroscopy, appears to be promising and can easily be extended to humans in many cases. Using pattern-recognition methods such as principal component analysis, 71 a combination of several biomarkers in peripheral fluids may provide greater sensitivity and selectivity than possible with individual markers.…”
Section: ± 74mentioning
confidence: 99%
“…Therefore, some of these enzymatic parameters such as activity of acetylcholinesterase have been used as biomarkers for the heavy metal monitoring (Matozzo et al, 2005). With the development of system biology, metabolomics, one of the techniques of system biology, has been widely applied in drug toxicity studies, disease diagnosis, functional genomics and environmental sciences (Wu et al, 2005;Waters et al, 2001;Marchesi et al, 2007;Gavaghan et al, 2002;Griffin et al, 2004;Brindle et al, 2002;Bundy et al, 2004;Viant et al, 2006a,b;Katsiadaki et al, 2009). The application of proton nuclear magnetic resonance (NMR) spectroscopy combined with pattern recognition methods to detect the responses of low molecular weight metabolites (<1000 Da) to toxicants or environmental contaminants has been demonstrated in both terrestrial vertebrate and invertebrate systems relevant to environmental toxicology (Bundy et al, 2002;Griffin et al, 2000;Fiehn, 2002).…”
Section: Introductionmentioning
confidence: 99%